Design and implementation of an artificial sports trainer - Fister, I.; Fister Jr., I.; Fister, D. (Computational intelligence in sports, 2018)
The artificial sports trainer bases on CI algorithms for enriching knowledge from data in databases that are obtained from sports activity datasets. These datasets are generated by wearable mobile devices (e.g., sports watches and smart phones) during sports training sessions. Indeed, the artificial sports trainer serves as an intelligent system capable of both knowledge discovery from data and decision-making based on these inputs. Thus, it automates the tasks of the real sports trainer in disciplines where a lot of data are generated by wearable mobile devices.